2020
DOI: 10.1136/bmjdrc-2019-000970
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perspectives on the barriers to referral after telescreening for diabetic retinopathy in communities

Abstract: Significance of this studyWhat is already known about this subject? ► Telemedicine has been applied in diabetic retinopathy (DR) screening. ► High rates of incomplete referral after telescreening for DR, and patients factors or healthcare system factors might contribute to the barriers for accessing the eye care services.What are the new findings?► Referral completion and perceived barriers to the referral were assessed in a large representative sample with vision-threatening DR (VTDR) from the communities aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…However, some studies noted limited sensitivity and specificity of smartphone examinations and lack of applications dedicated to screening. AI helped in the use of low-quality portable screening devices for high-quality assessments [ 117 ]. Smartphones needed a wide pupil for good-quality images [ 38 , 63 , 73 ]…”
Section: Resultsmentioning
confidence: 99%
“…However, some studies noted limited sensitivity and specificity of smartphone examinations and lack of applications dedicated to screening. AI helped in the use of low-quality portable screening devices for high-quality assessments [ 117 ]. Smartphones needed a wide pupil for good-quality images [ 38 , 63 , 73 ]…”
Section: Resultsmentioning
confidence: 99%
“…Low referral completion after undergoing DR tele-screening is a drawback that should be noted, one which is not unique to teleophthalmology and which has been noted in face-to-face appointments and for other medical disciplines. In a large study conducted by Zhu et al they found that the phenomenon of limited engagement is particularly common in the elderly and low education level populations and that lack of knowledge and a negative attitude toward telemedicine might be more prominent than logistic barriers in predicting incomplete referral, thus emphasizing the importance of proper education and raising awareness [32]. Similarly, improving patients' perception toward and promoting the use of teleophthalmology through proper education in low-income diabetic US population was also described [33].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Participants diagnosed with vision-threatening diabetic retinopathy (VTDR) after remote retinal image reading were referred to the superior medical institutions for further diagnosis and treatment. People with diabetes were classi ed as management in the CHSCs based on the diagnosis after telescreening and referrals [16,17].…”
Section: Shanghai Diabetic Eye Studymentioning
confidence: 99%
“…In addition, most of the known community management guidelines of DR are for high-income countries with high resource allocation, but no standardized management method for community population with DR currently exists in many developing countries including China [14,15]. A comprehensive management system for diabetic eye diseases (abbreviated as "the System" in the following text) has been established through the Shanghai Diabetic Eye Study (SDES) since 2015, which focuses on telescreening, referral, and management [16,17]. The new cooperation mode between CHSCs and superior medical institutions not only meets the eye health care of community people with diabetes but also effectively realizes the early screening, diagnosis, and intervention of DR.…”
Section: Introductionmentioning
confidence: 99%